"Engineering" innovation: Organizational factors affecting creativity and career satisfaction. Issue 1 (19th March 2019) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Increasing innovation is a challenge for organizations, especially in the public sector, to achieve better and more effective services. This paper uses a multi-level model to look at what organizational factors are involved in the engineering profession in Australia for innovation and thus employee satisfaction at work. Having a supportive leader and improving an innovative culture would increase a creative workplace environment, leading to staff engagement and retention, and ultimately to better impact and service. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.